Incomplete lineage sorting and ancient admixture, and speciation without morphological change in ghost-worm cryptic species - José Cerca; Angel G. Rivera-Colón; Mafalda S. Ferreira; Mark Ravinet; Michael D. Nowak; Julian M. Catchen; Torsten H. Struck (PeerJ, 2021)
Morphologically similar species, that is cryptic species, may be similar or quasi-similar owing to the deceleration of morphological evolution and stasis. While the factors underlying the deceleration of morphological evolution or stasis in cryptic species remain unknown, decades of research in the field of paleontology on punctuated equilibrium have originated clear hypotheses. Species are expected to remain morphologically identical in scenarios of shared genetic variation, such as hybridization and incomplete lineage sorting, or in scenarios where bottlenecks reduce genetic variation and constrain the evolution of morphology. Here, focusing on three morphologically similar Stygocapitella species, we employ a whole-genome amplification method (WGA) coupled with double-digestion restriction-site associated DNA sequencing (ddRAD) to reconstruct the evolutionary history of the species complex. We explore population structure, use population-level statistics to determine the degree of connectivity between populations and species, and determine the most likely demographic scenarios which generally reject for recent hybridization. We find that the combination of WGA and ddRAD allowed us to obtain genomic-level data from microscopic eukaryotes (∼1 millimetre) opening up opportunities for those working with population genomics and phylogenomics in such taxa. The three species share genetic variance, likely from incomplete lineage sorting and ancient admixture. We speculate that the degree of shared variation might underlie morphological similarity in the Atlantic species complex.